ENVIRONMENTAL QUALITY IN THE PERCEPTION OF RESIDENTS OF THE COMMUNITY OF SANTA RITA, BENJAMIN CONSTANT, AMAZONAS - dos Santos Moura, Anna Caroline; de Oliveira Gentil, Daniel Felipe; Montiel dos Santos Moura, Catharine; Lima, Renato Abreu (South American Journal of Basic Education, Technical and Technological, 2020)
The objective was to describe the environmental quality from the community residents' perception, aiming to contribute to the teaching of Environmental Sciences in Basic Education. To this end, interviews were conducted with 20 families of the community about quality, environmental quality and quality of life, which were conceptualized through adjectives related to their life and daily activities, evidencing that their practices contribute to maintain interdependence with the environment. so that both benefit from this relationship.